Empire and Politics in the Eastern and Western Civilizations Searching for a 'Respublica Romanosinica' - Ahn, Jaewon; Balbo, Andrea; Kim, Kihoon (Roma Sinica, 2022)
The volume includes the proceedings of the 2nd Roma Sinica conference held in 2019 and aims to compare some features of the ancient political thought in the Western classical tradition and in the Eastern ancient thought. The contributors propose new patterns of interpretation of the mutual interactions and proximities between these two cultural worlds and offer also a perspective of continuity between contemporary and ancient political thought.